2 thotsawat Sō̜sō̜ʻō̜. kap kānphatthanā ʻutsāhakam Thai (Samnakngān Sētthakit ʻUtsāhakam, 2011)
On accomplishments of the Office of Industrial Economics, and economic conditions and development of Thailand; volume commemorating 20th anniversary of the Office.